2020
DOI: 10.3389/fcell.2020.00133
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Gradients Yield Exceptionally Robust Steering Cues

Abstract: Chemotaxis is a widespread mechanism that allows migrating cells to steer to where they are needed. Attractant gradients may be imposed by external sources, or selfgenerated, when cells create their own steep local gradients by breaking down a prevalent, broadly distributed attractant. Here we show that chemotaxis works far more robustly toward self-generated gradients. Cells can only respond efficiently to a restricted range of attractant concentrations; if attractants are too dilute, their gradients are too … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…Both of these behaviors could be very important to help Dd cells to navigate complex hypoxic environments they encounter in the soil. In addition, our results are a confirmation of the ability of self-generated gradients to serve as very robust, long-lasting directional cues in environmental navigation, a property which has recently emerged in a variety of systems ( Cremer et al, 2019 ; Tweedy and Insall, 2020 ). Finally, our work goes beyond theses results as it demonstrates that oxygen can play the role of the attractant in self-generated gradients therefore potentially extending the physiological relevance of the use of such cues in collective migration.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Both of these behaviors could be very important to help Dd cells to navigate complex hypoxic environments they encounter in the soil. In addition, our results are a confirmation of the ability of self-generated gradients to serve as very robust, long-lasting directional cues in environmental navigation, a property which has recently emerged in a variety of systems ( Cremer et al, 2019 ; Tweedy and Insall, 2020 ). Finally, our work goes beyond theses results as it demonstrates that oxygen can play the role of the attractant in self-generated gradients therefore potentially extending the physiological relevance of the use of such cues in collective migration.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, the original experiments of Adler ( Adler, 1966 ) and more recent developments ( Cremer et al, 2019 ; Fu et al, 2018 ; Saragosti et al, 2011 ) on bacteria demonstrated that similar ingredients as the ones presented here can lead to front propagation in both 1d and 2d situations. Similarly, using an under agarose assay, it was demonstrated that self-generated gradients of degraded folate induce a group migration of cells in bands (in 1D) or rings (in 2D spots) up to 4 mm ( Tweedy and Insall, 2020 ). Beyond the dimensionality of the system, it was also shown that self-generated gradients allow cells to solve mazes by locally degrading an attractant that has a source at the exit of the maze ( Tweedy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The self-generated LPA (melanoma) and folate ( Dd ) gradients were modeled with a simple numerical model that was able to predict the steady wave. In particular, it predicted an invasive front where cells are exposed to a steep chemoattractant gradient, followed by a ‘trailing end’ where the gradient is shallow and fewer cells migrate with poor directionality(Tweedy & Insall, 2020). It also predicted that the wave may have a less marked front, and/or a smaller speed, or even vanishes if the cell density was too low due to insufficient chemoattractant removal.…”
Section: Discussionmentioning
confidence: 99%